Neuroprosthetics for Auricular Muscles: Neural Networks and Clinical Aspects - Liugan, Mikee; Zhang, Ming; Cakmak, Yusuf Ozgur (Frontiers in Neurology, 2018)
The mammalian external ear houses extrinsic and intrinsic auricular muscles. There are three extrinsic auricular muscles—the posterior, superior and anterior auricular muscles—and six intrinsic muscles—the helicis major and minor, tragicus, anti-tragicus, transverse and oblique muscles. These muscles have been considered vestigial in humans. However, numerous therapeutic and diagnostic wearable devices are designed to monitor and alleviate the symptoms of neurological disorders, brainstem injuries, emotional states, and auditory functions, by making use of the neural networks of the auricular muscles and their locations, which are easily accessible for ergonomic wearable biomedical devices. They can also serve as a bio-controller of human neuroprosthetics. The functionality of these auricular muscles remains elusive and requires further experimentation for a more in-depth understanding of their anatomy. The aims of this review are (1) to provide a detailed account of the neural networks of the extrinsic and intrinsic auricular muscles, (2) to describe diagnostic and therapeutic functions of these muscles as demonstrated in the current literature, and (3) to outline existing and potential neuroprosthetic applications making use of the auricular muscles and their neural networks.